2015
DOI: 10.1016/j.tree.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Selection on stability across ecological scales

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 75 publications
3
92
1
1
Order By: Relevance
“…See Pimm (1984), Logofet (2005), Ives and Carpenter (2007), Donohue et al (2013), and Borrelli et al (2015) for additional reviews on different stability concepts.…”
Section: Nestednessmentioning
confidence: 99%
“…See Pimm (1984), Logofet (2005), Ives and Carpenter (2007), Donohue et al (2013), and Borrelli et al (2015) for additional reviews on different stability concepts.…”
Section: Nestednessmentioning
confidence: 99%
“…Only recently have investigators begun to explore the synergism between these two perspectives, suggesting that food‐web topology and population stability combine to produce a single conceptual framework (Rooney & McCann ; Borrelli et al . ). These studies have suggested that species assemble in ways that maximize energy transfer (Milo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Borrelli et al . (), for example, suggested a non‐adaptive selection process governing the occurrence of modules (small topological components of communities). This process would act on intrinsic properties of population stability to produce a single consistent topological pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Our model dynamics is governed solely by the competition among species and in the absence of competition any species will reach a fixed carrying capacity K, accordingly it provides an example of evolution via nonadaptive selection as defined in Borrelli et al (2015). Upon speciation, the daughter species inherits its mother's traits up to small modifications, specifically, the strength of its competition with other species, as expressed by the relevant terms of the competition matrix.…”
Section: Summary and Discussionmentioning
confidence: 99%